Move your body, stay away from depression: a systematic review and meta-analysis of exercise-based prevention of depression in middle-aged and older adults - Zhao, Xiao-Dong; Oh, Sae-Sook; Zhang, Zheng; Wang, Chong (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to systematically assess the efficacy of exercise interventions in preventing depression among middle-aged and older adults. It further sought to dissect the impact of various intervention factors on the exercise-depression nexus within this demographic.MethodsWe conducted a comprehensive search across multiple databases including PubMed, Embase, Web of Science, and the Cochrane Library, spanning from their inception through April 2024. The initial search yielded several studies, from which 11 papers involving a total of 792 subjects were selected based on predetermined inclusion criteria.ResultsOur meta-analysis revealed a significant overall effect size (SMD = −3.64) with a 95% confidence interval of [−4.81, −2.48] and a p-value of <0.00001, underscoring the potent preventative impact of exercise on depressive symptoms in the target population. However, the studies exhibited substantial heterogeneity (I2 = 87%).ConclusionExercise interventions, particularly balance and gentle training as well as functional training, significantly reduce the risk of depression among middle-aged and older adults. The most pronounced effects were observed in group exercise settings and with exercise sessions lasting 30–40 min. Interventions of medium duration generally outperformed shorter-term interventions. Despite these promising results, the observed heterogeneity and other potential study limitations suggest a need for further research involving larger samples and more comprehensive study designs to refine and optimize exercise protocols for depression prevention in this population.